ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Putu Lisa Ernawatiningsih; Putu Ayu Meidha Suwandewi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2025)
The Indonesia Stock Exchange (IDX) is a capital market in Indonesia. The Indonesia Stock Exchange plays an important role as a means for people to invest, which is an alternative investment. For companies, the IDX helps companies to obtain additional capital by going public, namely the activity of offering shares or other securities carried out by issuers (companies that go public) to the public based on the procedures regulated by the Capital Market Law and its Implementing Regulations. Financial instruments traded on the capital market include shares, bonds, warrants, rights, convertible bonds, and various derivative products such as options (put or call). Company value is the price that buyers are willing to pay if the company is sold. The price of securities indicates the value of the company as an investor's assessment of the company's future profits and the quality of the company's management. This study aims to test and obtain empirical evidence of the influence of financial ratios and company size on company value in LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The population of this study is LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The sample in this study was 20 LQ45 companies determined based on the purposive sampling method with an observation period of 3 (three) years from 2021 to 2023, so the amount of data used was 60 data. The data analysis technique used to test the hypothesis is the Multiple Linear Analysis Technique. The results of the study indicate that Return On Equity (ROE) has a positive effect on company value. While Current Ratio (CR), Debt To Equity Ratio (DER), Total Turnover Ratio (TATO) and Company Size do not affect company valuea.